The Fayoum : history and guide. - Hewison, R. Neil (American University in Cairo Press, 2008)
The Fayoum, a large and exceptionally fertile depression in Egypt's Western Desert, some 90 kilometers southwest of Cairo, is a region both rich in history and outstanding in natural beauty. Its historical legacy includes temples, pyramids, and towns from the Middle Kingdom and the Ptolemaic Period, as well as churches, monasteries, and mosques from later times. Neil Hewison here outlines the history (and prehistory) of the Fayoum and its lakes, describes the agriculture and rural life of the region, then guides the visitor around the province site by site, never averse to taking an interesting.